A direct-to-drive neural data acquisition system - Kinney, Justin P.; Bernstein, Jacob G.; Meyer, Andrew J.; Barber, Jessica B.; Bolivar, Marti; Newbold, Bryan; Scholvin, Jorg; Moore-Kochlacs, Caroline; Wentz, Christian T.; Kopell, Nancy J.; Boyden, Edward S. (Frontiers in Neural Circuits, 2015)
Driven by the increasing channel count of neural probes, there is much effort being directed to creating increasingly scalable electrophysiology data acquisition systems. However, all such systems still rely on personal computers for data storage, and thus are limited by the bandwidth and cost of the computers, especially as the scale of recording increases. Here we present a novel architecture in which a digital processor receives data from an analog-to-digital converter, and writes that data directly to hard drives, without the need for a personal computer to serve as an intermediary in the data acquisition process. This minimalist architecture may support exceptionally high data throughput, without incurring costs to support unnecessary hardware and overhead associated with personal computers, thus facilitating scaling of electrophysiological recording in the future.